Avaliação sanitária do mutum-de-bico-vermelho (Crax blumenbachii) e do mutum-do-nordeste (Pauxi mitu) mantidos em cativeiro no estado de Minas Gerais, no período de 2011 a 2014 - Marcus Vinícius Romero Marques (2014)
Red-billed Curassow (Crax blumenbachii) and Alagoas Curassow (Pauxi mitu) in captivity in the State of Minas Gerais, Brazil, were evaluated for selected etiologies, aiming to the health assessment of these species. Twenty (6,55% - 20/305) curassows were positive for Plasmodium, by stained blood smear (Giemsa) and PCR (blood). All C. blumenbachii and P. mitu were negative (swab cloacal) for Aviadenovirus by PCR. However, young Pauxi mitu affected by fibrino-hemorrhagic tracheitis were positive for Aviadenovirus A, by PCR and confirmed by sequencing. All cloacal swabs were negative for Chlamydophila psittaci and Mycoplasma gallisepticum by PCR. Clostridium perfringens type A was isolated from 20.98% (64/305) birds, and cpb2 gene positive C. perfringens type A, which encodes for beta-2 toxin, was detected in 1.96% (6/305). Salmonella Saintpaul was isolated from three red-billed curassows (2.17% 3/138) and Salmonella Anatum was isolated from one Alagoas curassow (0.59% 1/167). Serology was performed only in Alagoas Curassows. By ELISA, antibodies to infectious bursal disease virus (IBDV) were demonstrated in 4.79% (8/167), to myeloid leukosis (subgroup J) in 3.59% (6/167), to avian reticuloendotheliosis virus in 4.79% (8/167), to avian Metapneumovirus in 1.79% (3/167) and avian Orthoreovirus in 10.17% (17/167). No antibodies were detected against avian leukosis virus (ALV). No antibodies to Mycoplasma gallisepticum or Mycoplasma synoviae were revealed by hemagglutination-inhibition (HI). However, antibodies to avian Paramyxovirus-1 were detected in 4.79% (8/167). This study indicates that the captive curassows in the captive do not present infection by relevant poultry pathogens. All efforts must be put forward in order to guarantee the conservation of these species, such as maintainance in biosecure premises.